2015
DOI: 10.3892/mmr.2015.4691
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces the proliferation of endothelial progenitor cells via upregulation of Apelin/APLNR/MAPK signaling

Abstract: Abstract. Endothelial progenitor cells (EPCs) can form new vessels through differentiation into endothelial cells (ECs), thus being important in the prevention of hypoxia/ischemia. Apelin can activate different signaling pathways through its receptor, APLNR, which regulate diverse biological functions, including cardiovascular function. However, the molecular mechanism by which Apelin mediates hypoxia-induced EPCs proliferation remain to be fully elucidated. The present study aimed to determine the role of Ape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…Overexpression of apelin in EPCs raises their angiogenic potential. These findings show the role of apelin in endothelial progenitor cell proliferation (Zhang et al, , ). Apelin‐overexpressing BMCs increases myocardial angiogenesis more efficiently than BMCs in post‐MI mice (Li et al, ).…”
Section: Apelin and Stem Cells: Effects On Cardiovascular Systemmentioning
confidence: 55%
See 2 more Smart Citations
“…Overexpression of apelin in EPCs raises their angiogenic potential. These findings show the role of apelin in endothelial progenitor cell proliferation (Zhang et al, , ). Apelin‐overexpressing BMCs increases myocardial angiogenesis more efficiently than BMCs in post‐MI mice (Li et al, ).…”
Section: Apelin and Stem Cells: Effects On Cardiovascular Systemmentioning
confidence: 55%
“…These findings suggest that apelin may be used as a promising therapeutic strategy in the treatment of oxidative stress associated metabolic diseases (Zhu et al, ; Than et al, ). Additionally, apelin has effects on angiogenesis in hypoxic conditions through increasing the proliferation of endothelial progenitor cells (Zhang et al, , ).…”
Section: Apelin and The Apj (Apelin Receptor Putative Receptor Protementioning
confidence: 99%
See 1 more Smart Citation
“…As the axis of several types of signal channels, mitogen-activated protein kinase (MAPK) cascade activation is a key member in the receipt of signals, which are transferred and carried by membrane receptors into the nucleus (6,7), which is key to numerous signaling channels associated with cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent studies have suggested that the overexpression of HIF-1a enhances the proliferation, invasion, cell survival, and in vitro capillary sprout formation of the EPC population. 24,32 In this study, therefore, we aimed to clarify the relation among intraplaque hypoxia, EPCs, and microvessels that cause IPH.…”
mentioning
confidence: 99%